PROPOSED PROGRAM STRATEGY OF CREATIVE SCHOOL FOR LECTURER DEVELOPMENT IN HE TRIDHARMA (CASE STUDY: CYAN.ID) (The Indonesian Journal of Business Administration, 2019)
Indonesia has a lot of workforce that significantly increase from time to time, which creates fresh potential power for Indonesia economic. Good workforce means that it should be developed with good education as well. But this development also has some constraints, which is the lecturer ability to cope with the rapid development are low. Even lecturer has main task to do Higher Education (HE) Tridharma, which is research, lecturing, and empowerment, these tasks are not completely done perfectly. The main issue is on how our development in education tend to forget the definitive of creativity. Creativity are often misconcepted and focus on concrete matter rather than abstract matter. This condition creates unbalanced mindset which created gap in problem solving and derived innovation for social empowerment. This is why Cyan.id are created to solve these mindset problems. This research will use several methods to determine the program strategy that applied for Cyan.id. The methods are Politics, Economics, Social, & Technology (PEST) analysis, Marketing mix (4P), Porter’s Five Forces, Key Success Factor, and Value Chain. The other methods to create valid data is to perform Minnesota Test of Creative Thinking (MTCT) and questionnaire to determine whether the creative school program is effective. These methods need to be done in order to create exact needs and strategy for Cyan.id and its customers.Keywords:Creative, Strategy, School, Tridharma, Education